2020
DOI: 10.1111/nph.16921
|View full text |Cite
|
Sign up to set email alerts
|

The ABI4‐RbohD/VTC2 regulatory module promotes reactive oxygen species (ROS) accumulation to decrease seed germination under salinity stress

Abstract: Salinity stress enhances reactive oxygen species (ROS) accumulation by activating the transcription of NADPH oxidase genes such as RbohD, thus mediating plant developmental processes, including seed germination. However, how salinity triggers the expression of ROSmetabolism-related genes and represses seed germination has not yet been fully addressed. In this study, we show that Abscisic Acid-Insensitive 4 (ABI4), a key component in abscisic acid (ABA) signaling, directly combines with RbohD and Vitamin C Defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 80 publications
(144 reference statements)
0
88
0
Order By: Relevance
“…Osmotic stress and ionic stress caused by saline-alkali stress further lead to the generation and accumulation of reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ) and hydroxyl radicals (OH − s). Luo et al (2021) addressed the mechanism of ROS production triggered by salinity. First, NaCl induces the expression of Abscisic Acid-Insensitive 4 (ABI4), which can enhance RbohD expression but repress VTC2 expression.…”
Section: Increasing Resistance To Oxidative Damage Via Antioxidant Enzymes and Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osmotic stress and ionic stress caused by saline-alkali stress further lead to the generation and accumulation of reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ) and hydroxyl radicals (OH − s). Luo et al (2021) addressed the mechanism of ROS production triggered by salinity. First, NaCl induces the expression of Abscisic Acid-Insensitive 4 (ABI4), which can enhance RbohD expression but repress VTC2 expression.…”
Section: Increasing Resistance To Oxidative Damage Via Antioxidant Enzymes and Antioxidantsmentioning
confidence: 99%
“…Then activated RbohD promotes ROS production while VTC2 repression impairs ROS scavenging. Therefore, this ABI4-RbohD/VTC2 regulatory module positively promotes ROS accumulation (Luo et al, 2021). Accumulated ROS will disrupt the normal physiological functions of cells, resulting in metabolic disorders.…”
Section: Increasing Resistance To Oxidative Damage Via Antioxidant Enzymes and Antioxidantsmentioning
confidence: 99%
“…We previously showed that ABI4 directly binds to the promoter of VTC2, inhibiting the transcription expression of VTC2, and then alleviating AsA biosynthesis [10]. ABI4 directly combines the key genes involved in ROS production and scavenging to modulate ROS metabolism during seed germination under salinity stress [38]. We found that AsA partially recovered the salt stress sensitivity of ABI4overexpressing plants, which had lower AsA content and more ROS accumulation.…”
Section: Introductionmentioning
confidence: 80%
“…As different from positive effects of GA, IAA, and CTK on seed germination, ABA is a primary hormone that promotes seed dormancy under drought stress ( Davies and Jones, 1991 ). ABA exerts its negative effects on seed germination by weakening the endosperm, restricting radicle expansion, and stimulating transcriptional factors that positively regulates seed dormancy ( Graeber et al, 2010 ; Luo et al, 2021 ). The current study reported that white clover seeds and seedlings demonstrated significant increase in endogenous IAA, GA, or ABA content with marked reduction in CTK content under drought stress ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%